An Overview of BSI Mobile Banking Services' Sharia Principles Compliance Implementation Perspective Maslahah Mursalah - Zidna, Rizka Rahmatllah; Mugiyati; Muhammad Raihan Syamil (Universitas Islam Negeri Alauddin Makassar, 2024)
Implementation of Shari'ah values is the distinguishing aspect between conventional and Shari'ah systems, including the development of Internet-based banking products. The technology that Islamic banks utilise also has to conform to Sharia rules, particularly as it relates to mobile banking. This research uses a literature review method with qualitative approaches with a focus on Sharia principles in DSN-MUI Fatwa No.10/DSN- MUI/VI/2000 regarding the use of Bank Syariah Indonesia's mobile banking service system and assessed with mashlahah mursalah. This research shows that the implementation of Shariah principles in BSI mobile services based on the DSN-MUI fatwa on wakalah has been carried out with the specified conditions. Reviewing the benefits obtained from mobile banking services shows that there are elements of goodness in it, so the analysis of online-based banking services at BSI Mobile is in compliance with the concept of Maṣlaḥah Mursalah according to Ash-Syatibi, as it has fulfilled the specified conditions.